Analisis Variasi Roller Weight Terhadap Performa Mesin Pada Sepeda Motor Vario 150 cc dengan Pertamax Turbo - Pangestu, Luthfi Daffa; Iwan Nugraha; Reza Setiawan (Jurnal Serambi Engineering, 2025)
Motorcycles have become an important means of personal transport for the general public. In daily use, engine performance is crucial to meet everyday mobility needs. Modern automatic motorcycles use a CVT (Continuously Variable Transmission) system, which is a key factor in engine performance within the transmission system. This study aims to observe differences in engine performance through variations in roller weight using a dynamometer and Pertamax Turbo fuel. The sample roll weight variations are the standard roll weight of a Vario 150cc motorcycle which is 15.6 grams, a racing roll weight of 14 grams and a 16 gram roll weight. The specific use of Pertamax Turbo fuel is to achieve maximum engine performance due to the perfect combustion that Pertamax Turbo can create with an RON of 98. This results in maximum power, acceleration and top speed.